Phylogenetic Analysis of Previously Nontypeable Hepatitis C Virus Isolates from Argentina - Gismondi, Maria Ines (2006)
Phylogenetic analysis of hepatitis C virus isolates from Argentina that were previously nontypeable by restriction fragment length polymorphism (RFLP) analysis revealed that they belong to genotype 1a. A substitution at position 107 (G3A), which is the landmark of these strains, was shown to be distributed among isolates worldwide. The RFLP patterns obtained for these isolates should be added to the ones reported for genotype 1 isolates.